2018
DOI: 10.1155/2018/8945130
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Volumetric Parameters in 11C-Choline PET/MR Are Superior PET Imaging Biomarkers for Primary High-Risk Prostate Cancer

Abstract: Purpose Positron emission tomography/magnetic resonance imaging (PET/MRI) can facilitate the use of noninvasive imaging biomarkers in clinical prostate cancer staging. Although multiparametric MRI is a widely used technique, the clinical value of simultaneous PET imaging remains unclear. This study aimed at investigating this issue. Methods Between January 2015 and December 2016, 31 high-risk prostate cancer patients underwent 11C-choline PET/MRI for staging purposes. Clinical characteristics and imaging param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“… Ferda et al [ 42 ] 2018 Czech Republic Retrospective 63.2 (47–78) 100 NA Restaging NA 18F-choline 100 Detection of disease PET/MRI with 18F-choline is a valuable tool in evaluation of restaging in patients with PCa, with high detection rate even in those with a low serum PSA level. Tseng et al [ 43 ] 2018 Taiwan Retrospective 70 (52–84) 31 30.56 ng/mL (47.5–591.9) Staging None 11C-Choline 31 Imaging interpretation Semiquantitative PET and MRI data are connected with the prognosis. Jena et al [ 44 ] 2018 India Retrospective 64 ± 1 82 NA Staging None 68Ga-PSMA-11 82 Detection of disease High diagnostic accuracy in primary tumors by using PET/MRI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Ferda et al [ 42 ] 2018 Czech Republic Retrospective 63.2 (47–78) 100 NA Restaging NA 18F-choline 100 Detection of disease PET/MRI with 18F-choline is a valuable tool in evaluation of restaging in patients with PCa, with high detection rate even in those with a low serum PSA level. Tseng et al [ 43 ] 2018 Taiwan Retrospective 70 (52–84) 31 30.56 ng/mL (47.5–591.9) Staging None 11C-Choline 31 Imaging interpretation Semiquantitative PET and MRI data are connected with the prognosis. Jena et al [ 44 ] 2018 India Retrospective 64 ± 1 82 NA Staging None 68Ga-PSMA-11 82 Detection of disease High diagnostic accuracy in primary tumors by using PET/MRI.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of them were focused on 68Ga-PSMA-11 ( n = 32 studies), while 2 were based on 18F-PSMA [ 31 , 33 ]. Radiolabeled choline PET/MRI was employed in the staging for 8/16 (50%) [ 11 14 , 17 , 29 , 43 , 53 ], while radiolabeled PSMA in 16/34 (47%) papers [ 16 , 18 , 27 , 31 , 35 37 , 40 , 44 49 , 54 ]. Conversely, 5/16 (31%) [ 9 , 21 , 39 , 42 , 51 ] and 11/34 (32%) articles [ 8 , 23 , 25 , 26 , 28 , 30 , 32 , 34 , 52 , 56 ] were focused on the resting phase for radiolabeled choline and PSMA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While 18 F isotopes have the benefits of longer half-lives thereby negating the need for an onsite cyclotron, their use has been limited significantly due to urinary excretion, which obfuscates the prostatic bed and periprostatic tissues. There have been relatively few studies of 11 C and 18 F choline PET/MRIs in CaP, which have shown promise in terms of improved accuracy per lesion as well as per patient in the PET/MRI model as compared to the mpMRI model only (27)(28)(29)(30).…”
Section: C-cholinementioning
confidence: 99%